Science and religious anthropology: a spiritually evocative naturalist interpretation of human life - Wildman, Wesley J. (Ashgate science and religion series, 2009)
Preliminaries -- Inquiry -- Religious anthropology and disciplinary stakeholders -- Cooperation between disciplinary stakeholders -- The very idea of Homo religiosus -- Naturalism -- Defining religious naturalism -- The meaning of naturalism in this project -- The pragmatic epistemology of inquiry -- Perspectives -- Evolution -- Evolutionary challenges to traditional religious anthropology -- Evolutionary status of religion -- Religion as an evolutionary byproduct -- Conclusion: Homo religiosus and evolution -- Groups -- Social dynamics of religion -- Evolutionary functions of corporate religiousness -- Explaining strange behavior -- Conclusion: Homo religiosus and groups -- Brains -- Religion and supernatural beliefs -- Cognitive error and religion -- Transformation of beliefs and behavior -- Conclusion: Homo religiosus and brains -- Bodies -- Bodies and sociality -- Bodies and morality -- Bodies and religious experiences -- Conclusion: Homo religiosus and bodies -- Sex -- Sex types and gender rolesu -- Male dominance -- Intimacy, sensuality, fantasy -- Conclusion: Homo religiosus and sex -- Habitat -- Environment and ecosystem habitat -- Technology and engineered habitat -- Symbols and value habitat -- Conclusion: Homo religiosus and habitat -- Findings -- Homo religiosus -- Homo religiosus : a synthetic portrayal -- The standing of alternative interpretations -- Religious anthropology, past and future